Utilization of diagnostic services at a municipal hospital in rural Nepal: Perspective from a general practitioner led primary care delivery - Bajaj Agrawal, Pawan Kumar; Giri, Baburam; Gupta, Priyanka; Nepali, Anjan; Parajuli, Suraj (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Municipal hospitals, being accessible and affordable, are essential to ensure universal health coverage. Several diagnostic services like laboratory investigations, X-ray imaging, ECG and POCUS are used in these primary care settings to ensure quality health delivery. Optimal utilization of diagnostic services is necessary for effective health expenditure in these government institutions which mostly depend upon government funding. In this study, we aimed to reflect upon the temporal trend of utilization of diagnostic services in a rural municipal hospital.Method: The study was carried out in Amppipal Municipal Hospital, in rural Gorkha over five fiscal years from July 2017 to June 2022. Yearly clinicians’ orders for different diagnostic services including laboratory investigations, X-rays, point-of-care ultrasound, and electrocardiogram were recorded. The proportion of total clients undergoing each of these services were evaluated.Result: The median number and median percentage of total yearly clients undergoing laboratory investigations, X-rays, electrocardiogram, and point-of-care ultrasound was respectively 7803(31.5%), 2385(11.1%), 279(1.3%) and 725(3.6%). The utilization of diagnostic services increased over the years. The net increment over five years in laboratory testing rate, X-rays, electrocardiogram, and point-of-care ultrasound was 35.15%, 80.00%, 776.29% and 85.49% respectively. While the net increment in the number of total annual clients over five years was 48.19%.Conclusion: This study reflected upon the utilization behavior of different diagnostic services in a primary care municipal hospital and suggested the trend of increasing utilization of all available diagnostic services over the years. It would serve as a reference to health system administrators and policy makers working in primary care service delivery.